Need for achievement and financial performance: a mediating role of board creativity - Victoria Makuya (Cogent Business & Management, 2024)
The purpose of this study is to examine the impact of need for achievement (NFA) and board creativity on financial performance. Furthermore, it attempts to investigate the mediating role of board diversity between need for achievement and financial performance. The assessment and estimation of how need for achievement and board creativity is associated with financial performance has not been previously provided. Using a self-administered survey to sample the Tanzanian microfinance institutions (MFI), the research measurement scale was adopted from previous studies, and data were collected from 189 MFIs. Drawing from McClelland, Institutional, Upper Echelons and agency theories' insights, the proposed conceptual model and associated hypotheses were formulated and tested using structural equation modeling. The empirical findings indicate that the need for achievement has a positive significant direct impact on financial performance. Also, the need for achievement has a positive significant impact on board creativity. Furthermore, board creativity has a positive significant impact on financial performance. Moreover, the study finds that board creativity positively mediates the relationship between need for achievement and financial performance. Therefore, this study has several empirical, theoretical, and practical implications and recommendations regarding the corporate governance literature, finance, and entrepreneurship practices.
Keywords: 650; Need for achievement; board creativity; financial performance; microfinance institutions; corporate governance